Anti-Xa guided enoxaparin dose adjustment improves pharmacologic deep venous thrombosis prophylaxis in burn patients. Issue 4 (June 2019) - Cronin, Brendan J.; Godat, Laura N.; Berndtson, Allison E.; Pham, Arielle; Kolan, Shobha; Box, Kevin; Lee, Jeanne G.; Costantini, Todd W.
Highlights: Burn patients are at high risk for developing deep vein thrombosis (DVT). A majority of burn patient did not achieve adequate pharmacologic DVT prophylaxis on standard dose enoxaparin. Performing enoxaparin dose adjustments improves pharmacologic DVT prophylaxis based on target anti-Xa levels. Alternate dosing strategies should be considered to improve pharmacologic DVT prophylaxis. Abstract: Introduction: Patients recovering from burn injury are at high risk of developing deep venous thrombosis (DVT). While 30-mg twice-daily enoxaparin is accepted as the standard prophylactic dose, recent evidence in injured patients suggests this dosing strategy may result in sub-optimal pharmacologic DVT prophylaxis. We hypothesized that standard enoxaparin dosing would result in inadequate DVT prophylaxis in burn patients. Methods: A retrospective review of an ABA-verified Burn center's registry from January 2012 — December 2016 identified patients with peak plasma anti-Xa levels to monitor the efficacy of pharmacologic DVT prophylaxis. Patients ≥18 years old were included if they received at least 3 doses of enoxaparin and had appropriately timed peak anti-Xa levels. We analyzed data including patient demographics, body weight, body mass index (BMI) and total body surface area burn (TBSA). Diagnosis of DVT was collected. Results: During the study period, 393 patients were screened with a plasma anti-Xa levels. Of the 157 patients that met inclusion criteria, 81 (51.6%) achieved target peak plasma anti-Xa levels (0.2–0.4 IU/mL) on standard 30-mg twice-daily prophylactic enoxaparin and 76 (48.4%) had sub-prophylactic levels. Sub-prophylactic patients were more likely to be male, have increased body weight and elevated BMI. 49 of the 76 sub-prophylactic patients received a dose-adjustment in order to reach target anti-Xa levels; 37 patients required 40 mg twice-daily, 10 required 50 mg twice-daily and 2 required 60 mg twice-daily. The overall DVT rate was 3.8%. Conclusions: The current recommended prophylactic dose of 30-mg twice-daily enoxaparin is inadequate in many burn patients. Alternate dosing strategies should be considered to increase the number of burn patients achieving target prophylactic anti-Xa levels. Determining whether prophylactic enoxaparin dose adjustment decreases DVT rates in burn injured patients should be evaluated in future prospective trials.